Assessment of paranasal sinuses in Magnetic Resonance Imaging of brain (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Headache is the most common indication for Magnetic Resonance Imaging (MRI).  But the minor ailments like paranasal sinusitis is often overlooked as it does not have specific discriminative characteristic and can imitate each type of primary headache. The purpose of this study was to evaluate the paranasal sinuses in patients undergoing MRI of brain. A cross-sectional hospital-based study of 118 patients was done from April to September 2014. The images were evaluated for presence of any abnormal findings in sinuses. A random probabilistic sampling was carried out. The sinuses were normal in 51 patients and abnormal in 67 patients. The most common abnormality was mucosal thickening followed by polyp, cyst, mass and fluid level respectively. 50 of 67 (74.6%) positive findings observed as mucosal thickening while polyp was seen in 13 patients (28.4%). Similarly, both mass and fluid level was seen in 3 (4.5%). The chi-square test showed no association between headache and abnormal sinus findings.